Re-evaluating particularly sensitive sea areas as an area-based management tool: advancing the implementation of the BBNJ agreement - Choi, Junghwan; Lim, Sangseop (Frontiers in Marine Science, 2025)
As a sectoral Area-Based Management Tool (ABMT) under the IMO regulatory framework, Particularly Sensitive Sea Areas (PSSAs) play a crucial role in preventing pollution from vessels. PSSAs allow coastal states to adopt Associated Protective Measures (APMs), including navigational restrictions and discharge controls, enabling more flexible and adaptive regulatory measures to prevent vessel-source marine pollution. The designation criteria and discharge control requirements for Special Areas under MARPOL73/78 are generally more stringent than those for PSSAs, particularly in Areas Beyond National Jurisdiction (ABNJ). This study analyzes the applicability and implementation of PSSAs as an ABMT within the framework of the BBNJ Agreement. It specifically addresses vessel-source marine pollution, a significant threat to marine ecosystems in ABNJ, and emphasizes the need for PSSAs as a legal tool to effectively prevent and mitigate this pollution. As a result, the study explores whether PSSAs can be adopted or applied as ABMTs under the BBNJ Agreement and presents improvement measures to enhance their effective implementation.